Blood–Brain Barrier Leakage Is Increased in Parkinson’s Disease - Al-Bachari, Sarah; Naish, Josephine H.; Parker, Geoff J. M.; Emsley, Hedley C. A.; Parkes, Laura M. (Frontiers in Physiology, 2020)
Background: Blood-brain barrier disruption has been noted in animal models of Parkinson’s disease (PD) and forms the basis of the vascular hypothesis of neurodegeneration, yet clinical studies are lacking. Objective: To determine alterations in blood-brain barrier integrity in PD, with comparison to cerebrovascular disease. Methods: Dynamic contrast enhanced magnetic resonance images were collected from 49 PD patients, 15 control subjects with cerebrovascular disease (control positive CP) and 31 healthy control subjects (control negative CN), with all groups matched for age. Quantitative maps of the contrast-agent transfer coefficient across the blood-brain barrier (Ktrans) and plasma volume (vp) were produced using Patlak analysis. Differences in Ktrans and vp were assessed with voxel-based analysis as well as in regions associated with PD pathophysiology. In addition, the volume of white matter lesions (WML) was obtained from T2-weighted fluid attenuation inversion recovery (FLAIR) images. Results: Higher Ktrans, reflecting higher blood-brain barrier leakage, was found in the PD group than in the CN group using voxel-based analysis; differences were most prominent in the posterior white matter regions. Region of interest analysis confirmed Ktrans to be significantly higher in PD than in CN, predominantly driven by differences in the substantia nigra, normal-appearing white matter, WML and the posterior cortex. WML volume was significantly higher in PD compared to CN. Ktrans values and white matter lesion volume were similar in PD and CP, suggesting a similar burden of cerebrovascular disease despite lower cardiovascular risk factors. Conclusion: These results show blood-brain barrier disruption in PD.